Long-distance HF radio waves propagation during the April 2023 geomagnetic storm by measurements in Antarctica, in Europe, and aboard RV Noosfera - Zalizovski, A.; Yampolski, Y.; Stanislawska, I.; Koloskov, O.; Budanov, O.; Bogomaz, O.; Gavrylyuk, B.; Sopin, A.; Reznychenko, A.; Kashcheyev, A.; Kashcheyev, S.; Lisachenko, V. (Ukrainian Antarctic Journal, 2023)
The paper aims at an experimental study of the mechanisms of long-distance high-frequency (HF) propagation and spatial and temporal variations of the ionospheric parameters during the first hours of a severe geomagnetic storm of April 23, 2023 by spatially separated measuring equipment located at the research vessel (RV) Noosfera, the Ukrainian Antarctic Akademik Vernadsky station (hereinafter Vernadsky), and the LOFAR observatory PL610 in Borowiec (Poland). High-frequency vertical and oblique sounding techniques of the ionosphere were used. Geospace measurements were carried out synchronously. During the first hours of the geomagnetic storm of April 23–24, 2023, unexpectedly well-correlated variations in the Doppler frequency shifts of HF signals emitted from Vernadsky were observed at the RV Noosfera and the PL610 station. Furthermore, variations in Doppler frequency shifts of HF signals strongly correlate with magnetic field records in Antarctica and Poland. Variations in the frequency of HF signal spectral components, distinguishable during storm conditions, are utilized to clarify the mechanism of long-distance HF propagation and estimate the vertical velocity of ionospheric layers. Signals of HF CHU time radio station (Canada) at 7850 and 14670 kHz were unexpectedly observed in all receiving sites. Most probably, the CHU station radio signals registered during the initial stage of the geomagnetic storm were scattered on the polar ovals’ ionospheric inhomogeneities and propagated further along the return (long arc of the great circle) paths. Redistribution of the ionospheric plasma during the geomagnetic storm leads to the formation of HF radio propagation channels absent under quiet conditions.